A Solar Heating and Cooling System in a Nearly Zero-Energy Building: A Case Study in China. (18th July 2017) - Sun, Zhifeng; Zhao, Yaohua; Xu, Wei; Zhang, Xinyu; Li, Huai; Wang, Min; He, Tao; Wang, Dongxu
Abstract : The building sector accounts for more than 40% of the global energy consumption. This consumption may be lowered by reducing building energy requirements and using renewable energy in building energy supply systems. Therefore, a nearly zero-energy building, incorporating a solar heating and cooling system, was designed and built in Beijing, China. The system included a 35.17 kW cooling (10-RT) absorption chiller, an evacuated tube solar collector with an aperture area of 320.6 m 2, two hot-water storage tanks (with capacities of 10 m 3 and 30 m 3, respectively), two cold-water storage tanks (both with a capacity of 10 m 3 ), and a 281 kW cooling tower. Heat pump systems were used as a backup. At a value of 25.2%, the obtained solar fraction associated with the cooling load was close to the design target of 30%. In addition, the daily solar collector efficiency and the chiller coefficient of performance (COP) varied from 0.327 to 0.507 and 0.49 to 0.70, respectively.